2015
DOI: 10.1111/febs.13193
|View full text |Cite
|
Sign up to set email alerts
|

Does the pressure dependence of kinetic isotope effects report usefully on dynamics in enzyme H‐transfer reactions?

Abstract: The temperature dependence of kinetic isotope effects (KIEs) has emerged as the main experimental probe of enzymatic H‐transfer by quantum tunnelling. Implicit in the interpretation is a presumed role for dynamic coupling of H‐transfer chemistry to the protein environment, the so‐called ‘promoting motions/vibrations hypothesis’. This idea remains contentious, and others have questioned the importance and/or existence of promoting motions/vibrations. New experimental methods of addressing this problem are emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The magnitude of ΔCP can therefore be used as an excellent proxy for changes to the enzyme FEL, and more specifically for the changes in vibrational modes during enzyme turnover (conformational sampling). Pressure effects are system specific but should perturb a large ΔCP as pressure affects the pre‐existing equilibrium of conformational states, favouring smaller volumes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of ΔCP can therefore be used as an excellent proxy for changes to the enzyme FEL, and more specifically for the changes in vibrational modes during enzyme turnover (conformational sampling). Pressure effects are system specific but should perturb a large ΔCP as pressure affects the pre‐existing equilibrium of conformational states, favouring smaller volumes .…”
Section: Introductionmentioning
confidence: 99%
“…Numerically fitting these data then gives Δ H ‡ , Δ S ‡ , Δ G ‡ , ΔCP, Δ V ‡ , Δβ ‡ and Δα ‡ reflecting the changes in enthalpy, entropy, Gibbs free energy, heat capacity, activation volume, compressibility and expansivity between the enzyme–substrate complex and the enzyme–transition state complex respectively. The enzyme kinetics for only a relatively few enzymes has been treated by combined p / T studies . In these cases, the p /T plane has not been fitted with a numerical model meaning at least ΔCP and ∆α ‡ are not determined.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier laser photoexcitation studies, which investigated the temperature dependence of the KIEs, showed that both H-transfer reactions proceed by tunnelling and are coupled to promoting vibrations in the enzyme-substrate complex [100]. In addition, the KIEs associated with both the hydride and proton transfer reactions decrease significantly at higher pressures, which suggests that the generic pressure response of hydride and proton transfers are likely to be similar [90]. It has been proposed that the role of light in the overall reaction is to overcome the barrier for the highly unfavourable hydride transfer chemistry [100].…”
Section: A Paradigm Model System-light-activated Enzymatic H-transfer Chemistrymentioning
confidence: 96%
“…Since the zero-point energy, which arises from the high-energy stretching frequency of the breaking bond, is largely invariant with pressure (over the experimental range) [86,87], while donor-acceptor fluctuations can be affected, pressure-dependent KIEs are indicative of quantum tunnelling [88,89]. Unfortunately, no simple trends have emerged between the pressure-and temperature-dependence of KIEs [90]. For example, the KIE of morphinone reductase (MR) was found to increase with pressure while ∆∆H ‡ remained constant, while both the KIE and ∆∆H ‡ decreased with pressure in aromatic amine dehydrogenase (AADH).…”
Section: Temperature-dependent Kies and The Role Of Fast Dynamicsmentioning
confidence: 99%
“…Structural and functional studies of oxidases , oxygenases and dehydrogenases are also reported. Other papers in the issue include studies of redox reactions in electron transfer flavoprotein and photoreceptors , enzyme inhibition for drug development , flavoenzyme for production of useful chemicals , regulation of riboflavin biosynthesis , and the use of physical tools and principles for interpreting protein dynamics and hydride transfer reactions .…”
mentioning
confidence: 99%